Obesity-compromised immunity in post-COVID-19 condition: a critical control point of chronicity - Jang, Soonwoo; Hong, Wooyoung; Moon, Yuseok (Frontiers in Immunology, 2024)
Post-COVID-19 syndrome is recognized as a multifactorial disorder, with persistent presence of viral antigens, discordant immunity, delayed viral clearance, and chronic inflammation. Obesity has emerged as an independent risk factor for both SARS-CoV-2 infection and its subsequent sequelae. In this study, we aimed to predict the molecular mechanisms linking obesity and post-COVID-19 distress. Viral antigen-exposed adipose tissues display remarkable levels of viral receptors, facilitating viral entry, deposition, and chronic release of inflammatory mediators and cells in patients. Subsequently, obesity-associated inflammatory insults are predicted to disturb cellular and humoral immunity by triggering abnormal cell differentiation and lymphocyte exhaustion. In particular, the decline in SARS-CoV-2 antibody titers and T-cell exhaustion due to chronic inflammation may account for delayed virus clearance and persistent activation of inflammatory responses. Taken together, obesity-associated defective immunity is a critical control point of intervention against post-COVID-19 progression, particularly in subjects with chronic metabolic distress.Established risk factors for SARS-CoV-2 infection include advanced age, diabetes, and metabolic syndrome (1). Obesity has been associated with an increased risk of SARS-CoV-2 infection, as well as an increased likelihood of needing intensive care and invasive mechanical ventilation. Obesity emerged as the predominant comorbidity among healthcare workers who were hospitalized in 14 US states, as reported by the COVID-19-associated Hospitalization Surveillance Network (2). Obesity has been recognized as an independent risk factor for the onset of . Although there appears to be a non-linear correlation between body mass index (BMI) and the severity of COVID-19 (4), multiple studies have indicated that individuals with a BMI over 25 kg/m2 experienced